2008
DOI: 10.1136/hrt.2006.110023
|View full text |Cite
|
Sign up to set email alerts
|

Increased granzyme B production from peripheral blood mononuclear cells in patients with acute coronary syndrome

Abstract: These results suggest that granzyme B might play an important role in triggering acute coronary events by inducing apoptosis and the degradation of atherosclerotic coronary plaques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 32 publications
1
18
0
Order By: Relevance
“…GrB is found in all regions of the atherosclerotic plaque in advanced atherosclerosis, where it appears to be produced by foam cells and macrophages (6,7). Plasma levels of GrB are also significantly elevated in atherosclerosis, with highest levels in patients with unstable plaques (8,9).…”
mentioning
confidence: 97%
“…GrB is found in all regions of the atherosclerotic plaque in advanced atherosclerosis, where it appears to be produced by foam cells and macrophages (6,7). Plasma levels of GrB are also significantly elevated in atherosclerosis, with highest levels in patients with unstable plaques (8,9).…”
mentioning
confidence: 97%
“…29 Furthermore, a recent study has suggested a link between GZMB and unstable angina pectoris in which mononuclear cells from unstable angina pectoris patients exhibited greater GZMB production compared with cells from stable angina pectoris or healthy controls. 30 As GZMB has been previously found to retain its activity in plasma, 52 it is not unreasonable to propose a mechanism whereby chronic inflammation with macrophage infiltration and mast cell activation could lead to increased GZMB levels in and around the vessel wall. GZMB then cleaves ECM components such as fibrillin-1, contributing to the loss of elastic lamellae, medial degeneration, vessel wall instability, and subsequent aneurysm formation, after which further assault by GZMB on the adventitial layer that maintains the structural integrity of the vessel could lead to rupture of the aorta.…”
Section: Granzyme B In Aortic Aneurysm 1045mentioning
confidence: 99%
“…29 Furthermore, elevated GZMB production is observed in peripheral blood mononuclear cells isolated from patients with unstable angina pectoris compared with cells from patients with stable angina pectoris. 30 The current study used a well-established mouse model of angiotensin II (Ang II)-induced AAA. 31 In this model, macrophage accumulation in the media of the suprarenal aorta and dissection precede the formation of aneurysm and atherosclerosis in Ang II-infused apolipoprotein E-knockout (APOE-KO) mice.…”
mentioning
confidence: 99%
“…13,14 Granulation tissue formed after myocardial infarction (MI) contains chronic inflammatory cells, and in recent studies, the activated Fas/FasL system and elevated levels of TNF-α released from inflammatory cells contributed to LV remodeling after AMI. 15,16 Interestingly, in our previous report we suggested that granzyme B plays an important role in triggering ACS by degrading coronary plaques, 17 amd we hypothesized that apoptosis-related molecules contribute to LV remodeling after AMI by inducing apoptosis and matrix degradation. In the present study, we focused on the role of granzyme B in LV remodeling after AMI.…”
mentioning
confidence: 99%